Targeting indigenous Schizosaccharomyces japonicus for genotype exploration and organic acid degradation analysis - Chen, Qiling; Wang, Chunxiao; Zhang, Zhanyan; Yang, Zhangyu; Zhou, Wenya; He, Jiaojiao; Song, Angxin; Wu, Yuangen; Qiu, Shuyi; Han, Lizhen (Frontiers in Microbiology, 2025)
Schizosaccharomyces japonicus belongs to fermentative non-Saccharomyces yeast, which has been reported to be predominant in the late stage of natural wine fermentation, and can coexist with S. cerevisiae. This study targeted the indigenous S. japonicus strains found in Guizhou, China, to explore their genotype diversity, and to further analyze their fermentation properties especially on the degradation capacity of malic acid. Seven microsatellite loci were developed including GA1, CG3, SyGAA2, C11, SaGAA1, C12, and TG2, and 43 genotypes were identified from 63 S. japonicus strains. All S. japonicus strains showed high malic acid reduction rate (higher than 90%) by initial metabolic analysis, except FBKL2.9SZJ-43 showing medium malic acid reduction rate (89.47%). The highest malic acid reduction rate was found in FBKL2.9SZJ-37 (98.64%). Ten S. japonicus strains were selected for further simulated fermentations based on their genotype, flocculation, and organic acid degradation traits. Among them, FBKL2.9SZJ-37 and FBKL2.9SZJ-55 showed good fermentation ability, strong malic acid degradation capacity, and relative weak tartaric acid degradation performance under both simulated fermentation conditions. Further fermentations using Rosa sterilis, Rosa roxbunghii Tratt juice, and Cabernet Sauvignon, verified the fermentation characteristics of the two S. japonicus strains when compared to S. cerevisiae. Especially for FBKL2.9SZJ-37, it showed good ethanol production, stronger glycerol formation and acid degradation ability, with malic acid reduction rate being 60.50, 64.98 and 98.32% in fermentations of three fruits, respectively. This study displays initial explorations on genotyping and fermentation application of indigenous S. japonicus especially for malic acid type fruit wine making, which would help to the development and application of potential excellent non-Saccharomyces yeast sources.